EFFECT OF COMPRESSION RATIO ON PERFORMANCE OF A HYDROGEN BLENDED CNG-DIESEL DUAL FUEL ENGINE (Journal of Mechanical Engineering, 2015)
Compression ratios of the engine considerably affect the performance and emission behavior of an engine.The paper discusses about effect of compression ratios on the operating parameters such as brake specific fuelconsumption (BSFC), brake specific energy consumption (BSEC), brake thermal efficiency (BTE) and volumetricefficiency on a stationary diesel-CNG dual fuel engine by adding hydrogen fraction as a combustion booster. Theexhaust emission behavior of the engine is also presented. Addition of hydrogen in CNG has given better resultsthan diesel-CNG dual fuel operation of the engine. The volumetric efficiency and emissions like NOx are theparameters which needed attention towards this study. The paper presents experimental results and analyzes them.